The prevention of low back disorders in divers - Narita, T.; Kaneoka, K. (Sports injuries and prevention, 2015)
During competitive diving events, divers jump up from 1 to 3 m springboards or 5-10 m platforms and dive into the water. The impact forces are very large in the water entry phase, and therefore, the divers experience a great deal of physical stress. This chapter is comprised of four sections on the prevention of low back pain(LBP) in divers. The first section is an introduction. The second section describes the very high incidence rate of LBP in Japanese elite junior divers. The third section details the importance of shoulder flexibility and age as critical factors for the prevention of LBP in elite junior divers. The fourth section describes investigations on the influence of the shoulder angle on entry alignment and compares the differences in entry phase alignment between the divers in the LBP diver group and non-LBP diver group. The results showed a negative correlation (r=-0.623) between the shoulder flexion angle and trunk extension angle for the entry phase. Four of 13 male divers experienced LBP. The trunk angle showed a significant difference between the LBP group (210.4±5.7°) and no-LBP group (199.9±9.0°). Our results suggested that shoulder flexibility is an important factor in the prevention of LBP in elite male junior divers